2020
DOI: 10.3390/biom10010086
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Peculiarities of In Planta Synthesis of Isoprenoid and Aromatic Cytokinins

Abstract: The biosynthesis of aromatic cytokinins in planta, unlike isoprenoid cytokinins, is still unknown. To compare the final steps of biosynthesis pathways of aromatic and isoprenoid cytokinins, we synthesized a series of nucleoside derivatives of natural cytokinins starting from acyl-protected ribofuranosyl-, 2′-deoxyribofuranosyl- and 5′-deoxyribofuranosyladenine derivatives using stereoselective alkylation with further deblocking. Their cytokinin activity was determined in two bioassays based on model plants Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This is consistent with the notion that only cytokinin bases have real biological activity, whereas their ribosides are mostly the inactive transport forms of these hormones and either cannot bind to cytokinin receptors or, even when binding, are unable to activate them [ 44 ]. Although ribonucleoside 12a demonstrated some GUS activity, mainly with the AHK3 Arabidopsis receptor, and the activity of cytokinin ribosides in biotests has been previously described [ 45 ], this residual activity was presumably due to their enzymatic conversion to free bases in vivo (see also the discussion below).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This is consistent with the notion that only cytokinin bases have real biological activity, whereas their ribosides are mostly the inactive transport forms of these hormones and either cannot bind to cytokinin receptors or, even when binding, are unable to activate them [ 44 ]. Although ribonucleoside 12a demonstrated some GUS activity, mainly with the AHK3 Arabidopsis receptor, and the activity of cytokinin ribosides in biotests has been previously described [ 45 ], this residual activity was presumably due to their enzymatic conversion to free bases in vivo (see also the discussion below).…”
Section: Resultsmentioning
confidence: 96%
“…The structure of the heterocyclic ribonucleoside base undoubtedly affects the efficiency of ribose cleavage [ 45 ]. In this work, we also observed that the presence of some substituents at C 2 apparently made it difficult to detach the ribofuranose residue, which blocked the cytokinin activity of riboside compound.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds have been shown to interact with the gut microbiota, immune system, and neurotransmitter systems, thereby influencing brain function. Phytochemicals such as polyphenols, carotenoids, flavonoids, and terpenoids have been identified as having potential therapeutic implications for various neurological disorders [ 19 ].
FIGURE 1 Modulatory effects of phytochemicals on the gut–brain axis.
…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that GBA is essential for the onset and course of a number of neurological conditions, such as PD, MS, depression, anxiety, and ASD [ 1 ]. The gut microbiota, composed of the gastrointestinal tract’s resident bacteria, is a crucial element of the GBA that may impact behavior and brain function through diverse pathways [ 19 ]. An imbalance in the makeup of the gut microbiota, or dysbiosis, has been linked to a number of neurological conditions, suggesting that modulating the gut microbiota may have potential therapeutic implications for these conditions [ 23 ].…”
Section: Introductionmentioning
confidence: 99%